(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The International English Language Testing System (IELTS) is a globally recognized exam that assesses English proficiency for academic, professional and immigration purposes. Structurally, the IELTS exam comprises four sections—Listening, Reading, Writing and Speaking—each targeting distinct language competencies. It is administered in two formats: the Academic module, tailored for higher education and professional certification, and the General Training module, which assesses practical language skills for workplace and social contexts. This article explores key strategies to enhance reading skills for the IELTS exam, focusing on comprehension techniques, vocabulary expansion and time management.